2017
DOI: 10.1158/1538-7445.am2017-4421
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4421: IGF2 regulates mitochondrial cell energy phenotype and biogenesis in TNBC cells

Abstract: Triple-negative breast cancer (TNBC) is very aggressive, resistant to chemotherapy and more likely to relapse, causing the worst prognosis. African American (AA) women suffer higher incidence and mortality of TNBC due to the expression of high levels of Insulin Growth Factor 2 (IGF2) which promotes tumor progression, metastasis, and chemoresistance. Also, it has been established that functional mitochondria and mitochondrial DNA (mtDNA) are essential for cancer cell growth. Mutations and/or reductions in mtDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, our recently published experimental finding and other clinical studies have demonstrated a functional impact for IGF2 on human and mouse embryo development [ 20 , 24 , 25 ]. Furthermore, recent reports about adult neuronal culture-derived cell lines have also demonstrated that IGF2 increases mitochondrial functional activity by reducing oxidative stress, as well as by increasing immunofluorescence staining intensity for mitochondria and increasing mitochondrial membrane potential [ 26 , 27 ]. Despite these numerous basic studies, the potential application of IGF2 is relatively unexplored, so little is known at the cellular and molecular level about how manipulation of IGF2 levels in for example oocytes from aged females may confer improvements in embryonic growth or even overall pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our recently published experimental finding and other clinical studies have demonstrated a functional impact for IGF2 on human and mouse embryo development [ 20 , 24 , 25 ]. Furthermore, recent reports about adult neuronal culture-derived cell lines have also demonstrated that IGF2 increases mitochondrial functional activity by reducing oxidative stress, as well as by increasing immunofluorescence staining intensity for mitochondria and increasing mitochondrial membrane potential [ 26 , 27 ]. Despite these numerous basic studies, the potential application of IGF2 is relatively unexplored, so little is known at the cellular and molecular level about how manipulation of IGF2 levels in for example oocytes from aged females may confer improvements in embryonic growth or even overall pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%